Radical Islam in Southeast Asia: Rhetoric and reality in the Middle Eastern connection - Gunn, Geoffrey C. (Journal of contemporary Asia, 1986)
The study explores whether the upsurge in fundamentalist attitudes reported in certain Islamic circles in Southeast Asia has been actively promoted/endorsed by Iran and to what degree, and at what level, Gadaffi of Libya has sought to intervene in Islam and/or liberationist/separatist issues in Southeast Asia. Resonance Gadaffiism as a liberationist force has struck with the target Muslim peoples, fronts and state actors in this region. Contours of Islamic challenge in Malaysia and Indonesia. (DÜI-Sen)